The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1177/088840648500800403
|View full text |Cite
|
Sign up to set email alerts
|

Regular and Special Educators

Abstract: Communication breakdowns between regular and special educators integrating students with handicaps into the regular education classroom have been associated with differences in professional orientation. The extent of these differences has not been well defined. In this study, 128 regular education teachers and 133 special educators from 21 school districts responded to a questionnaire addressing management, professional, and educational concerns relating to handicap integration (i.e., mainstreaming). The two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The first problem with consultation is that a lack of congruence may exist between suggestions for classroom interventions made by consultants and general educators' understanding of those suggestions (Abidin, 1975;Gans, 1985). The training and experience of special education teachers generally is geared to individualized instructional settings, which are very different from the demands and pressures of the typical general education classroom.…”
Section: Problems In the Practice Of Consultationmentioning
confidence: 99%
“…The first problem with consultation is that a lack of congruence may exist between suggestions for classroom interventions made by consultants and general educators' understanding of those suggestions (Abidin, 1975;Gans, 1985). The training and experience of special education teachers generally is geared to individualized instructional settings, which are very different from the demands and pressures of the typical general education classroom.…”
Section: Problems In the Practice Of Consultationmentioning
confidence: 99%
“…In the 1980s, according to Cassidy (1982), integration was not new in the education profession, especially during the teaching and learning process (See the study conducted by Gans (1985) on integration attitudes and implications). It is revealed that integration is about examining involvement in technology based on past and present activities to shape future activities.…”
Section: Integration (Phenomenon) In Educationmentioning
confidence: 99%
“…It is revealed that integration is about examining involvement in technology based on past and present activities to shape future activities. Integration gives teachers a chance to analyse difficult situations, tackle the problem, and to think differently in finding solutions to problems (Gans, 1985). Integration thus involves personal thinking in finding the solution.…”
Section: Integration (Phenomenon) In Educationmentioning
confidence: 99%